Experimental Analysis for Determination of the Optimum Use of Natural and Artificial Waste Material in Concrete: Utilization of Natural and Artificial Waste Material for Lightweight Concrete Construction (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The concrete is most important civil engineering construction material. Concrete consist of various ingredients like Cement, Coarse aggregate and Fine aggregate with wc ratio 0.46 in proportion. Cement acts as binding material now a day’s partly replaced with fly ash. Fly ash is a waste product of power plants. The disposal of fly ash is big problem now a day. An experimental analysis is proposed to replace cement aggregate by the artificial and natural waste product like fly ash and coconut shell in different proportion. Coconut shell is hard and light weight material. The properties of coconut shell and aggregate is examined and the suitability of coconut shell aggregate in construction is also examined. The main objective is to analyse the usefulness of fly ash, coconut shell and glass as a construction material and to prepare lightweight concrete by using coconut shell as coarse aggregate. The experimental study is carried out on strength characteristics of M30 concrete with replacement of 10 20 of cement, coarse aggregate and fine aggregate by fly ash, coconut shell and glass. The water cement ratio is 0.46 by using compressive, tensile strength of concrete at, 03,07 28 days are determined with experimental analysis and the results are compared with conventional concrete.